Conductive Additive for Si/Mesoporous Carbon Anode for Li-Ion Batteries: Commercial Graphite vs Carbon Black C65. (7th August 2015) - Rezqita, Arlavinda; Hamid, Raad; Schwarz, Sabine; Kronberger, Hermann; Trifonova, Atanaska
Abstract : Silicon is a promising candidate for anodes in lithium-ion batteries (LIB) due to its high theoretical capacity. However, Si has low electrical conductivity (theoretical: 6.7 x 10 -4 S cm -1 ). Proper conductive additive is needed in order to improve the electrical conductivity of Si-based anodes. Here we focus on applying two commercial conductive addictives: graphite and carbon black Super C65 for silicon-mesoporous carbon (Si/MC) composite anodes. The structure and morphology of the electrodes were characterized by nitrogen adsorption, scanning electron microscopy (SEM), and focus ion beam/transmission electron microscopy (FIB/TEM). Furthermore, the electrochemical performance of the electrodes was characterized by cyclic voltammetry, galvanostatic charge/discharge tests, and impedance spectroscopy. In principles, our work could be effective for the choice of conductive additives to improve the electrical performance of Si/MC anodes.